Asymmetric hafnium metallocene
By using a catalyst combined with an asymmetric hafnium metallocene and an activator, the problem of insufficient polymer MWCDI in the prior art is solved, and the polymer performance is improved, which is suitable for a variety of applications.
Patent Information
- Application Number
- CN202380054111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-04
- Publication Date
- 2025-03-04
AI Technical Summary
Prior Art In developing novel and improved materials and/or methods for forming polymers, it is difficult to effectively improve the molecular weight comonomer distribution index (MWCDI) of the polymer, thus limiting the performance of polymers in a variety of applications.
Asymmetric hafnium metallocene was used as a catalyst to prepare a polyolefin polymer with improved MWCDI by contacting the asymmetric hafnium metallocene with the activator. The process includes using the asymmetric hafnium metallocene represented by structure (I) and reacting with the olefin monomer in polymerization.
By improving the MWCDI of polymers, the improved performance of polymers in film and other applications is achieved, and this method can effectively prepare polymers with larger molecular weight, enhancing the application value of polymers.
Smart Images

Figure CN119562957A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate to asymmetric hafnium metallocenes, catalyst compositions comprising the same, methods of making and using the same, and polyolefins made therefrom. Background Art
[0002] Metallocenes can be used in a variety of applications, including as polymerization catalysts. Polymers can be used in a variety of products, including membranes, etc. Polymers can be formed by reacting one or more types of monomers in a polymerization reaction. The industry is constantly working to develop new and improved materials and / or methods that can be used to form polymers. Summary of the invention
[0003] The present disclosure provides various embodiments including the following.
[0004] An asymmetric hafnium metallocene represented by structure (I):
[0005]
[0006] Where R 1 is (C1-C8)alkyl; and each X is independently a leaving group.
[0007] A metallocene catalyst composition comprises an asymmetric hafnium metallocene and an activator.
[0008] A method for preparing a metallocene catalyst composition comprises contacting an asymmetric hafnium metallocene with an activator.
[0009] A method for preparing a polyolefin polymer comprises polymerizing at least one olefin monomer with a metallocene catalyst composition to prepare the polyolefin polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0011] Figure 2 Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0012] Figure 3A Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0013] Figure 3B Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0014] Figure 4 Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0015] Figure 5 Shown is a graph of data for determining the molecular weight comonomer distribution index (MWCDI) according to various embodiments of the present disclosure.
[0016] Figure 6 Shown is a data graph of molecular weight comonomer distribution index (MWCDI) versus density according to various embodiments of the present disclosure.
[0017] Figure 7 Shown is a data graph of molecular weight comonomer distribution index (MWCDI) versus density according to various embodiments of the present disclosure. DETAILED DESCRIPTION
[0018] Asymmetric hafnium metallocenes are discussed herein. Advantageously, these asymmetric metallocenes can be used to prepare, for example, catalyst compositions. These catalyst compositions can be used to prepare polymers having improved (i.e., larger) molecular weight comonomer distribution indexes (MWCDI) compared to other polymers prepared by other metallocenes. These polymers are desired for many applications (including films, etc.). Therefore, it is advantageous to provide improved MWCDI. Such polymers are advantageous for many applications.
[0019] The asymmetric hafnium metallocene can be represented by structure (I):
[0020]
[0021] Where: R 1 is (C1-C8) alkyl; and each X is independently a leaving group. As shown in structure (I), the upper cyclopentadienyl ring is R 1 The lower cyclopentadienyl ring is unsubstituted. 1 The cyclopentadienyl group is substituted, and the other cyclopentadienyl ring is unsubstituted, so the metallocene can be called an asymmetric metallocene.
[0022] One or more embodiments of the present disclosure provide that R 1 is (C1-C8) alkyl. One or more embodiments of the present disclosure provide that R 1 is (C1-C7) alkyl. One or more embodiments of the present disclosure provide that R 1 is (C1-C6) alkyl. One or more embodiments of the present disclosure provide that R 1is (C2-C5) alkyl. One or more embodiments of the present disclosure provide that R 1 is (C3-C4) alkyl. One or more embodiments of the present disclosure provide that R 1 is (C3) alkyl. (C3) alkyl may be branched or linear. As used herein, "Pr" and "normal Pr" refer to -CH2CH2CH3. One or more embodiments of the present disclosure provide that R 1 The (C4)alkyl group may be an isobutyl group.
[0023] Embodiments of the present disclosure provide that X is a leaving group. One or more embodiments provide that X is selected from alkyl, aryl, hydride and halogen. One or more embodiments provide that X is selected from halogen, (C1-C5) alkyl, CH2SiMe3 and benzyl. One or more embodiments provide that X is selected from alkyl and halogen. One or more embodiments provide that X is Cl. One or more embodiments provide that X is methyl.
[0024] Examples of X include halogen ions, hydrides, (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12 ) aryl, (C7 to C 20 ) alkylaryl, (C1 to C 12 ) alkoxy, (C6 to C 16 )aryloxy, (C7 to C8)alkylaryloxy, (C1 to C 12 ) fluoroalkyl, (C6 to C 12 ) fluoroaryl and (C1 to C 12 ) hydrocarbons containing heteroatoms and their substituted derivatives; one or more embodiments include hydrides, halides, (C1 to C6) alkyls, (C2 to C6) alkenyls, (C7 to C 18 )alkylaryl, (C1 to C6)alkoxy, (C6 to C 14 ) aryloxy, (C7 to C 16 )alkyl aryloxy, (C1 to C6) alkyl carboxylate, (C1 to C6) fluorinated alkyl carboxylate, (C6 to C 12 ) aryl carboxylate, (C7 to C 18 )alkylarylcarboxylates, (C1 to C6)fluoroalkyl, (C2 to C6)fluoroalkenyl and (C7 to C 18 ) fluoroalkylaryl; one or more embodiments include hydride, chloride, fluoride, methyl, phenyl, phenoxy, benzoyloxy, tosyl, fluoromethyl and fluorophenyl; one or more embodiments include (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12) aryl, (C7 to C 20 ) alkylaryl, substituted (C1 to C 12 ) alkyl, substituted (C6 to C 12 ) aryl, substituted (C7 to C 20 ) alkylaryl and (C1 to C 12 ) containing heteroatoms, (C1 to C 12 ) containing heteroatoms and (C1 to C 12 ) containing heteroatoms; one or more embodiments include chloride, fluoride, (C1 to C6) alkyl, (C2 to C6) alkenyl, (C7 to C 18 ) alkylaryl, halogenated (C1 to C6) alkyl, halogenated (C2 to C6) alkenyl and halogenated (C7 to C 18 ) alkylaryl; one or more embodiments include fluoride, methyl, ethyl, propyl, phenyl, methylphenyl, dimethylphenyl, trimethylphenyl, fluoromethyl (monofluoromethyl, difluoromethyl and trifluoromethyl) and fluorophenyl (monofluorophenyl, difluorophenyl, trifluorophenyl, tetrafluorophenyl and pentafluorophenyl).
[0025] Other non-limiting examples of X groups include amines, phosphines, ethers, carboxylates, dienes, hydrocarbon groups with 1 to 20 carbon atoms, fluorinated hydrocarbon groups (e.g., -C6F5(pentafluorophenyl)), fluorinated alkyl carboxylates (e.g., CF3C(O)O-), hydrides, halogen ions, and combinations thereof. Other examples of X ligands include alkyl groups such as cyclobutyl, cyclohexyl, methyl, heptyl, tolyl, trifluoromethyl, tetramethylene, pentamethylene, methylene, methoxy, ethoxy, propoxy, phenoxy, bis(N-methylaniline), dimethylamido, and dimethylphosphoryl, etc. In one embodiment, two or more X form a part of a fused ring or ring system. In one or more embodiments, X can be a leaving group selected from the group consisting of chloride, bromide, (C1 to C5) and 2-hydroxy-1-hydroxy- ... 10 ) alkyl, (C2 to C 12 ) alkenyl, carboxylate, acetylacetonate, and alcoholate. In one or more embodiments, X is methyl.
[0026] The asymmetric hafnium metallocenes discussed herein can be prepared by contacting a hafnium complex with an alkali metal complex to prepare the asymmetric hafnium metallocene. The asymmetric hafnium metallocenes discussed herein can be prepared by methods used to prepare known metallocenes (e.g., using conventional solvents, reaction conditions, reaction times, and isolation procedures).
[0027] Alkali metal complexes can be represented by one of the following structures:
[0028]
[0029] Where M' is lithium, sodium or potassium, and R 1 As defined in this article.
[0030] One or more embodiments provide that the hafnium complex can be represented by one of the following structures:
[0031]
[0032] Where R 1 As defined in this article.
[0033] One or more embodiments provide a method for preparing an asymmetric metallocene (e.g., wherein each X is Cl) comprising: contacting the asymmetric metallocene with two molar equivalents of an organomagnesium halide of formula RMg(halide) or one molar equivalent of R2Mg, wherein R is (C1-C5)alkyl, CH2SiMe3 or benzyl; and the halide is Cl or Br, to prepare an asymmetric metallocene of structure (I), wherein each X is (C1-C5)alkyl, CH2SiMe3 or benzyl. One or more embodiments provide that X is (C1-C5)alkyl, CH2SiMe3 or benzyl. As used herein, all references to the Periodic Table of the Elements and its Groups refer to the NEW NOTATION as published in HAWLEY'S CONDENSED CHEMICAL DICTIONARY, Thirteenth Edition, John Wiley & Sons, Inc. (1997) (reproduced with permission from IUPAC), unless reference is made to the previous IUPAC form marked with Roman numbering (which also appears therein) or unless otherwise mentioned.
[0034] As used herein, "alkyl" includes straight chain, branched chain, and cyclic alkane radicals lacking one hydrogen. Thus, for example, CH3 ("methyl") and CH2CH3 ("ethyl") are examples of alkyl radicals.
[0035] As used herein, "alkenyl" includes straight chain, branched chain, and cyclic alkene groups lacking one hydrogen group; alkynyl includes straight chain, branched chain, and cyclic ethynyl groups lacking one hydrogen group.
[0036] As used herein, "aryl" groups include phenyl, naphthyl, pyridyl and other groups whose molecules have ring structures characteristic of benzene, naphthylene, phenanthrene, anthracene, etc. It should be understood that "aryl" groups can be C6 to C 20 Aryl groups. For example, a C6H5 aromatic structure is a "phenyl" and a C6H42 aromatic structure is a "phenylene". An "aralkyl" group is an alkyl group with a pendant aryl group. It should be understood that an "aralkyl" group can be (C7 to C 20Aralkyl Groups. "Alkaryl" is an aryl group having one or more pendant alkyl groups.
[0037] As used herein, "alkylene" includes straight chain, branched, and cyclic hydrocarbon groups lacking two hydrogens. Thus, CH2 ("methylene") and CH2CH2 ("ethylene") are examples of alkylene groups. Other groups lacking two hydrogen groups include "arylene" and "alkenylene".
[0038] As used herein, the term "heteroatom" includes any atom selected from the group consisting of: B, Al, Si, Ge, N, P, O and S. A "heteroatom-containing group" is a hydrocarbon group containing heteroatoms and may contain one or more of the same heteroatoms or different heteroatoms, and may contain 1 to 3 heteroatoms in a particular embodiment. Non-limiting examples of heteroatom-containing groups include groups (monovalent and divalent groups) of imines, amines, oxides, phosphines, ethers, ketones, oxazoline heterocycles, oxazoline and thioethers.
[0039] As used herein, the term "substituted" means that one or more hydrogen atoms in the parent structure have been independently replaced with a substituent atom or group.
[0040] The asymmetric hafnium metallocene discussed herein can be used to prepare catalyst compositions. These compositions comprise the asymmetric hafnium metallocene discussed herein and an activator. One or more embodiments specify that the activator is an alkylaluminoxane, such as methylaluminoxane. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can, for example, activate the complex or catalyst component by generating a cationic species of the catalyst component. For example, this can include capturing at least one leaving group, for example, the "X" group described herein, from the metal center of the complex / catalyst component (e.g., the asymmetric hafnium metallocene of structure (I). The activator may also be referred to as a "co-catalyst". As used herein, "leaving group" refers to one or more chemical moieties that are combined with a metal atom and can be captured by an activator, thereby generating a substance that is active for olefin polymerization. Various catalyst compositions, such as olefin polymerization catalyst compositions are known in the art, and different known catalyst composition components can be used. Different amounts of known catalyst composition components can be used for different applications.
[0041] The asymmetric hafnium metallocenes discussed herein can be used to prepare spray-dried compositions. As used herein, a "spray-dried composition" refers to a composition comprising a number of components that has undergone a spray-drying process. Various spray-drying methods are known in the art and are suitable for forming the spray-dried compositions disclosed herein. One or more embodiments provide that the spray-dried composition comprises a conditioning composition.
[0042] In one or more embodiments, the spray drying process may include atomizing a composition comprising the asymmetric hafnium metallocene discussed herein. Many other known components may be used in the spray drying process. Atomizers such as atomizing nozzles or centrifugal high-speed disks, for example, may be used to produce a spray or dispersion of composition droplets. The droplets of the composition may then be rapidly dried by contact with an inert dry gas. The inert dry gas may be any gas, such as nitrogen, that is not reactive under the conditions employed during atomization. The inert dry gas may encounter the composition at the atomizer, which produces a stream of droplets on a continuous basis. The dried composition particles may be captured from the process in a separator, such as a cyclone separator, which may separate the formed solid from a gas mixture of a drying gas, a solvent, and other volatile components.
[0043] For example, the spray-dried composition can have a free-flowing powder form. After the spray-drying process, the spray-dried composition and many known components can be used to form a slurry. The spray-dried composition can be used together with a diluent to form a slurry suitable for, for example, olefin polymerization. In one or more embodiments, the slurry can be merged with one or more other catalysts or other known components before being delivered in a polymerization reactor.
[0044] In one or more embodiments, a spray-dried composition can be formed by contacting spray-dried activator particles (such as spray-dried MAO) with a solution of an asymmetric hafnium metallocene as discussed herein. Such solutions can typically be prepared in, for example, an inert hydrocarbon solvent and are sometimes referred to as a conditioning solution. Such spray-dried compositions comprising contacting a conditioning solution of an asymmetric hafnium metallocene with spray-dried activator particles (such as spray-dried MAO) can be prepared in situ in a feed conduit to a gas phase polymerization reactor by contacting the conditioning solution with a slurry of spray-dried activator particles (typically in mineral oil).
[0045] Various spray drying conditions can be used for different applications. For example, the spray drying process can utilize a drying temperature of 75° C. to 185° C. Other drying temperatures are also possible, wherein the temperature may depend on the metallocene and activator particles. Various sizes of the orifice of the atomizing nozzle employed during the spray drying process can be used to obtain different particle sizes. Alternatively, for other types of atomizers such as disks, the rotation speed, disk size, and number / size of holes can be adjusted to obtain different particle sizes. One or more embodiments provide that fillers can be used in the spray drying process. Different fillers and their amounts can be used for various applications.
[0046] The asymmetric hafnium metallocene discussed herein (e.g., a catalyst composition, such as a spray-dried hafnium metallocene composition) can be used to prepare a polymer. For example, the asymmetric hafnium metallocene can be activated (i.e., with an activator) to prepare a catalyst. One or more embodiments provide that the spray-dried composition comprises an activator. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can activate a complex or catalyst component, such as by generating a cationic species of a catalyst component, for example, to provide a catalyst. An activator may also be referred to as a "cocatalyst". The activator may include a Lewis acid or a non-coordinating ion activator or an ionizing activator, or any other compound including a Lewis base, an alkyl aluminum and / or a conventional cocatalyst. The activator includes methylaluminoxane (MAO) and modified methylaluminoxane (MMAO), etc. One or more embodiments provide that the activator is methylaluminoxane. Activation conditions are well known in the art. Known activation conditions can be used.
[0047] The molar ratio of the metal (e.g., aluminum) in the activator to the hafnium in the asymmetric hafnium metallocene can be from 1500: 1 to 0.5: 1, from 300: 1 to 1: 1, or from 150: 1 to 1: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene is at least 75: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene is at least 100: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene is at least 150: 1.
[0048] The asymmetric hafnium metallocene discussed herein and a plurality of other components may be supported on the same or independent carriers, or one or more of the components may be used in a non-supported form. The use of the carrier may be achieved by any technique used in the art. One or more embodiments provide for the use of a spray drying process. The carrier may be functionalized. One or more embodiments provide for the spray dried composition to include a carrier.
[0049] "Carrier" may also be referred to as "support", and refers to any carrier material, including porous carrier materials (such as talc), inorganic oxides and inorganic chlorides. Other carrier materials include resin carrier materials (such as polystyrene), functionalized or cross-linked organic carriers (such as polystyrene divinyl benzene polyolefins or polymeric compounds), zeolites, clays or any other organic or inorganic carrier materials, etc., or mixtures thereof.
[0050] The support material includes an inorganic oxide including a Group 2, 3, 4, 5, 13 or 14 metal oxide. Some preferred supports include silica, fumed silica, alumina, silica-alumina and mixtures thereof. Some other supports include magnesium oxide, titanium oxide, zirconium oxide, magnesium chloride, montmorillonite, phyllosilicates, zeolites, talc, clays and the like. Moreover, combinations of these support materials may be used, such as silica-chromium, silica-alumina, silica-titania and the like. One or more embodiments provide that the support is silica, and one or more embodiments provide that the support is hydrophobic fumed silica. One or more embodiments provide that the support is dehydrated silica. Additional support materials may include porous acrylic polymers, nanocomposites, aerogels, spherulites and polymer beads. An example of a support is available under the trade name Cabosil TM Fumed silica obtained from TS-610, or other TS-series or TG-series supports available from Cabot Corporation. Fumed silica is typically silica having a particle size of 7 to 30 nanometers that has been treated with dimethylsilyl dichloride such that a majority of the surface hydroxyl groups are capped.
[0051] The asymmetric hafnium metallocene discussed herein (e.g., catalyst composition / spray-dried composition) and olefins can be contacted under polymerization conditions to prepare polymers, e.g., polyolefin polymers. The polymerization process can be a solution polymerization process, a suspension polymerization process, a slurry polymerization process, and / or a gas phase polymerization process. The polymerization process can utilize known equipment and reaction conditions, e.g., known polymerization conditions. The polymerization process is not limited to any particular type of polymerization system. The polymer can be used in many articles, such as films, fibers, nonwoven fabrics and / or woven fabrics, extruded articles, and / or molded articles.
[0052] One or more embodiments provide for the use of a gas phase reactor system to prepare the polymer. One or more embodiments provide for the use of a single gas phase reactor, for example, as opposed to a series of reactors. In other words, the polymerization reaction occurs in only one reactor. For example, a fluidized bed reactor can be used to prepare the polymer. Gas phase reactors are known, and known components can be used in fluidized bed reactors.
[0053] As used herein, "olefins" which may be referred to as "alkenes" refer to linear, branched or cyclic compounds comprising carbon and hydrogen and having at least one double bond. As used herein, when polyolefins, polymers and / or copolymers are referred to as comprising olefins (e.g., prepared from olefins), the olefins present in the polymers or copolymers are olefins in polymerized form. For example, when it is said that the ethylene content of a copolymer is 75% to 95% by weight, it is understood that the polymer units in the copolymer are derived from ethylene in the polymerization reaction, and based on the gross weight of the polymer, the derived units are present in 75% to 95% by weight. Higher alpha-olefins refer to alpha-olefins having 3 or more carbon atoms.
[0054] The polyolefin prepared with the composition discussed herein can be prepared from olefin monomers, such as ethylene (i.e., polyethylene) or propylene (i.e., polypropylene), and other materials provided herein, wherein the polyolefin is a homopolymer prepared only from olefin monomers (e.g., prepared with 100% by weight ethylene or 100% by weight propylene). Alternatively, the polyolefin prepared with the composition discussed herein can be prepared from olefin monomers, such as ethylene (i.e., polyethylene), and straight or branched higher alpha-olefin monomers containing 3 to 20 carbon atoms. Examples of higher alpha-olefin monomers include, but are not limited to, propylene, butene, pentene, 1-hexene and 1-octene. Examples of polyolefins include ethylene-based polymers with at least 50% by weight ethylene, including ethylene-1-butene, ethylene-1-hexene and ethylene-1-octene copolymers, etc. One or more embodiments provide that based on the total weight of the polymer, the polymer may contain 50% by weight to 99.9% by weight of units derived from ethylene. All individual values and subranges of 50 wt % to 99.9 wt % are included; for example, based on the total weight of the polymer, the polymer may include a lower limit of 50 wt %, 60 wt %, 70 wt %, 80 wt % or 90 wt % of units derived from ethylene to an upper limit of 99.9 wt %, 99.7 wt %, 99.4 wt %, 99 wt %, 96 wt %, 93 wt %, 90 wt % or 85 wt % of units derived from ethylene. By the total weight of the polymer, the polymer may include 0.1 wt % to 50 wt % of units derived from comonomers. One or more embodiments provide that ethylene is used as a monomer and hexene is used as a comonomer.
[0055] As mentioned, polymers prepared with the compositions disclosed herein can be prepared in a fluidized bed reactor. The fluidized bed reactor can have a reaction temperature of 10°C to 130°C. All individual values and subranges from 10°C to 130°C are included; for example, the fluidized bed reactor can have a reaction temperature of 10°C, 20°C, 30°C, 40°C, 50°C, or 55°C at a lower limit to 130°C, 120°C, 110°C, 100°C, 90°C, 80°C, 70°C, or 60°C at an upper limit.
[0056] The fluidized bed reactor can have an ethylene partial pressure of 30 pounds per square inch (psi) to 250 psi, including all individual values and subranges from 30 to 250; for example, the fluidized bed reactor can have an ethylene partial pressure of 30 psi, 45 psi, 60 psi, 75 psi, 85 psi, 90 psi, or 95 psi on the lower limit and 250 psi, 240 psi, 220 psi, 200 psi, 150 psi, or 125 psi on the upper limit.
[0057] One or more embodiments provide that ethylene is used as a monomer and hexene is used as a comonomer. The fluidized bed reactor may have a comonomer to ethylene molar ratio of 0.0001 to 0.100, for example, C6 / C2. All individual values and subranges from 0.0001 to 0.100 are included; for example, the fluidized bed reactor may have a comonomer to ethylene molar ratio of 0.0001, 0.0005, 0.0007, 0.001, 0.0015, 0.002, 0.007, 0.010, 0.016, or 0.024 to an upper limit of 0.100, 0.080, or 0.050. One or more embodiments provide that no comonomer is utilized.
[0058] When hydrogen is used in the polymerization process, the fluidized bed reactor can have, for example, a hydrogen to ethylene molar ratio (H2 / C2) of 0.00001 to 0.90000. All individual values and subranges from 0.00001 to 0.90000 are included; for example, the fluidized bed reactor can have a H2 / C2 with a lower limit of 0.00001, 0.00005, or 0.00008 to an upper limit of 0.90000, 0.500000, 0.10000, 0.01500, 0.00700, or 0.00500. One or more embodiments provide that hydrogen is not utilized.
[0059] Conventional gel permeation chromatography can be used to determine multiple polymer properties. For example, a chromatographic system consisting of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) is used to determine weight average molecular weight (Mw), number average molecular weight (Mn), Z average molecular weight (Mz) and Mw / Mn (PDI). The autosampler oven compartment is set to 160°C, and the column compartment is set to 150°C. The column used is 4 Agilent "Mixed A" 30cm 20 micron linear mixed bed columns. The chromatographic solvent used is 1,2,4 trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.
[0060] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards ranging from 580 g / mol to 8,400,000 g / mol and arranged in 6 "cocktail" mixtures with at least ten times intervals between individual molecular weights. The standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 grams of polystyrene standards were prepared in 50 milliliters of solvent, and for molecular weights less than 1,000,000, 0.05 grams of polystyrene standards were prepared in 50 milliliters of solvent. The polystyrene standards were pre-dissolved at 80°C with gentle stirring for 30 minutes, then cooled and the room temperature solution transferred to a 160°C autosampler dissolution oven to cool for 30 minutes. The polystyrene standard peak molecular weight was converted to polyethylene molecular weight using Formula 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let.), 6, 621 (1968)):
[0061] M 聚乙烯 =A× (M 聚苯乙烯 ) B (Formula 1)
[0062] Where M is the molecular weight, A has a value of 0.4061, and B equals 1.0.
[0063] A fifth-order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.
[0064] Total plate counts for the GPC column set were performed with decane, which was introduced into the blank sample via a micropump controlled by the PolymerChar GPC-IR system. The plate count for the chromatography system should be greater than 18,000 for four Agilent "Mixed A" 30 cm 20-micron linear mixed bed columns.
[0065] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set at 2 mg / ml and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen by the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 2 hours under "low speed" shaking.
[0066] Mn was determined according to Equations 2 to 4 based on GPC results using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer using the PolymerChar GPCONE software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve for point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation.
[0067]
[0068] To monitor the deviation over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly calibrate the pump flow (flow) for each sample by (标称) ): The RV of the corresponding decane peak in the sample (RV (FM样品) ) with the decane peak within the narrow standard calibration (RV (FM校准) ) were compared. It was then assumed that any changes in the decane marker peak time were related to the flow rate (flow rate (有效) ). After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated according to Equation 5. Processing of the flow marker peak is done via the PolymerChar GPCONE software. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.5% of the nominal flow rate.
[0069] Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (Formula 5)
[0071] IR5 GPC Octene Composition Calibration. Calibration for IR5 detector dosing is performed using at least ten ethylene-based polymer standards (octene as comonomer) produced in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor over a single site metallocene catalyst with narrow SCB distribution and known comonomer content (e.g., by 13 C NMR method, Qiu et al., Anal. Chem. 2009, 81, 8585-8589) in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor over a single-site metallocene catalyst, the known monomer content ranges from homopolymer (0 SCB / 1000 total C) to about 40 SCB / 1000 total C, where total C = carbon in the main chain + carbon in the branch chain. Each standard has a weight average molecular weight of 36,000 g / mole to 126,000 g / mole as measured by GPC. Each standard has a molecular weight distribution (Mw / Mn) of 2.0 to 2.5. The SCB standard trimer properties are shown in Table A.
[0072] Table A: "Copolymer" Standards
[0073] Weight % comonomer IR5 Area Ratio SCB / 1000Total C M Mw / Mn 23.1 0.2411 28.9 37,300 2.22 14.0 0.2152 17.5 36,000 2.19 0.0 0.1809 0.0 38,400 2.20 35.9 0.2708 44.9 42,200 2.18 5.4 0.1959 6.8 37,400 2.16 8.6 0.2043 10.8 36,800 2.20 39.2 0.2770 49.0 125,600 2.22 1.1 0.1810 1.4 107,000 2.09 14.3 0.2161 17.9 103,600 2.20 9.4 0.2031 11.8 103,200 2.26
[0074] The “IR5 Area Ratio” (or “IR5 Area Response”) of the “Baseline-Subtracted Area Response of the IR5 Methyl Channel Sensor” to the “Baseline-Subtracted Area Response of the IR5 Measurement Channel Sensor” was calculated for each of the “Copolymer” standards. 甲基通道面积 / IR5 测量通道面积 ”)” (including standard filters and filter wheels supplied by PolymerChar: Part No. IR5_FWM01 as part of the GPC-IR instrument). A linear fit of the wt% comonomer frequency versus the “IR5 Area Ratio” was constructed in the form of Equation 6 below:
[0075] Weight % comonomer = A0 + [A1 x (IR5 甲基通道面积 / IR5 测量通道面积 )](Formula 6)
[0076] Where A0 is the "wt% Comonomer" intercept at "IR5 Area Ratio" of zero, and A1 is the slope of "wt% Comonomer" versus "IR5 Area Ratio" and represents the increase in wt% Comonomer according to "IR5 Area Ratio". For the narrow PDI and narrow SCBD standard materials, the IR5 Area Ratio is equal to the IR5 Height Ratio.
[0077] Melt strength measurements were performed on a Goettfert Rheotester 71.97 (Goettfert Inc.; Rock Hill, SC) attached to a Goettfert Rheotester 2000 capillary rheometer. The molten sample (approximately 25 to 30 grams) was fed with a Goettfert Rheotester 2000 capillary rheometer with a length of 30 mm, a diameter of 2.0 mm, and an aspect ratio (length / diameter) of 15, equipped with a flat angle of incidence (180 degrees). After the sample was allowed to equilibrate at 190°C for 10 minutes, the piston was operated at a constant piston speed of 0.265 mm / second. The standard test temperature is 190°C. The sample was uniaxially stretched to a set of accelerating wheels located 100 mm below the die, with an acceleration of 2.4 mm / s 2 The force exerted on the wheel is recorded as a function of the take-up speed of the wheel.
[0078] The following conditions were used in melt strength measurements: plunger accelerator 0.265 mm / sec; wheel acceleration = 2.4 mm / s; capillary diameter = 2.0 mm; capillary length = 30 mm; and barrel diameter = 12 mm. Melt strength is reported as the average plateau force before chain breakage (cN).
[0079] The rheological properties of each composition were analyzed by dynamic mechanical spectroscopy (DMS) using an advanced rheological expansion system (ARES) equipped with 25mm stainless steel parallel plates under nitrogen purge. Constant temperature dynamic frequency sweeps (see Tables 9 and 10) were performed in the range of 0.1rad / s to 100rad / s at 190°C under nitrogen. Samples of approximately 25mm diameter x 3.3mm thickness were cut from compression molded blocks (see below). The sample was placed on the lower plate and allowed to balance for five minutes. The plate was then closed to a gap of 2.0mm, and the sample was adjusted to a diameter of 25mm. Before starting the test, the sample was balanced at 190°C for five minutes. Complex viscosity was measured at a constant strain amplitude of 10%. The stress response is analyzed in terms of amplitude and phase, from which the storage modulus (G'), loss modulus (G"), dynamic viscosity η*, and tan delta can be calculated. The viscosities (V0.1 and V100) are recorded. Note that V0.1 is the complex viscosity at 0.1 rad / s (190°C) and V100 is the complex viscosity at 100 rad / s (190°C). The viscosity is reported in Pascal-seconds (Pa·s).
[0080] For each composition, samples were prepared by compression molding approximately 2.3 g of material in a 2 in. by 3 in. by 3 mm thick TEFLON coated mold sleeve at 190° C. for five minutes at 10 MPa pressure and then quenching between cooled platens (15° C. to 20° C.) for two minutes.
[0081] The comonomer distribution or short chain branching distribution in ethylene / α-olefin copolymers can be characterized as normal (also referred to as having a Ziegler-Natta distribution), inverse or flat. Several reported methods are used to quantify broad orthogonal composition distribution (BOCD). Herein, a simple straight line fit is used so that the normal or inverse nature of the comonomer distribution can be quantified by the molecular weight comonomer distribution index (MWCDI), which is the slope of the linear regression of the comonomer distribution measured by composition GPC, where the x-axis is Log (MW), and the y-axis is the weight percent of the comonomer. Figure 1 A data graph for determining the MWCDI for Example 1-2 (MWCDI = 6.58), and a data graph for determining the MWCDI for Comparative Example A-2 (MWCDI = 3.60) are shown, as shown in Table 1 of the Examples section of the present application. Reverse comonomer distribution is defined when MWCDI>0, and normal comonomer distribution is defined when MWCDI<0. When MWCDI=0, the comonomer distribution is said to be flat. In addition, MWCDI quantifies the magnitude of the comonomer distribution. Comparing two polymers with MWCDI>0, the polymer with a larger MWCDI value is defined as having a larger, i.e., increased BOCD; in other words, the polymer with a larger MWCDI value has a larger reverse comonomer distribution. For example, as reported in Table 1, respectively, the polymer prepared with Examples 1-2 has an increased BOCD compared to the polymer prepared with Comparative Example A-2. A polymer with a relatively large MWCDI (i.e., BOCD) can provide improved physical properties, such as improved film performance, compared to a polymer with a relatively small MWCDI.
[0082] Polymers prepared with the compositions disclosed herein can have a MWCDI of 0.10 to 10.00, including all individual values and subranges from 0.10 to 10.00; for example, a polymer can have a MWCDI of a lower limit of 0.10, 0.50, or 1.00 to an upper limit of 10.00, 9.00, 8.00, 8.50, or 8.35.
[0083] The polymers prepared using the compositions disclosed herein may have a hardness of 0.8700 g / cm 3 Up to 0.9700g / cm 3 Density. Including 0.8700g / cm 3 Up to 0.9700g / cm3 All individual values and subranges of; for example, a polymer may have a lower limit of 0.8700 g / cm 3 , 0.9000g / cm 3 、0.9100g / cm 3 、0.9150g / cm 3 , 0.9200g / cm 3 or 0.9250g / cm 3 The upper limit is 0.9700g / cm 3 , 0.9600g / cm 3 , 0.9500g / cm 3 、0.9450g / cm 3 、0.9350g / cm 3 or 0.9300g / cm 3 Density. The density can be measured according to ASTM D792.
[0084] The polymer prepared with the composition disclosed herein may have a melt index (I2) of 0.0 dg / min to 1500 dg / min. I2 can be determined according to ASTM D1238 (190 ° C, 2.16 kg). It should be noted that I2 of 0.0 dg / min can be referred to as "no flow". All individual values and subranges from 0.0 dg / min to 1500 dg / min are included; for example, the polymer may have a lower limit of 0.0 dg / min, 0.05 dg / min, 0.07 dg / min, 0.10 dg / min, 0.20 dg / min, 0.30 dg / min or 0.50 dg / min to an upper limit of 1500 dg / min, 1200 dg / min, 1000 dg / min, 500 dg / min, 200 dg / min, 120 dg / min or 100 dg / min I2.
[0085] The polymer prepared with the composition disclosed herein can have a weight average molecular weight (Mw) of 10,000 g / mol to 1,000,000 g / mol. All individual values and subranges of 10,000 g / mol to 1,000,000 g / mol are included; for example, the polymer can have a lower limit of 10,000 g / mol, 50,000 g / mol, or 100,000 g / mol to an upper limit of 1,000,000 g / mol, 750,000 g / mol, or 500,000 g / mol. As known in the art, Mw can be determined by gel permeation chromatography (GPC). GPC is discussed herein.
[0086] The polymers prepared with the compositions disclosed herein can have a number average molecular weight (Mn) of 5,000 g / mol to 300,000 g / mol. All individual values and subranges of 5,000 g / mol to 300,000 g / mol are included; for example, the polymer can have a Mn with a lower limit of 5,000 g / mol, 20,000 g / mol, or 40,000 g / mol to an upper limit of 300,000 g / mol, 250,000 g / mol, or 200,000 g / mol. Mn can be determined by GPC.
[0087] The polymers prepared with the compositions disclosed herein may have a Z-average molecular weight (Mz) of 40,000 g / mol to 2,000,000 g / mol. All individual values and subranges of 40,000 g / mol to 2,000,000 g / mol are included; for example, the polymer may have a Mz with a lower limit of 40,000 g / mol, 100,000 g / mol, or 250,000 g / mol to an upper limit of 2,000,000 g / mol, 1,800,000 g / mol, or 1,650,000 g / mol. Mz may be determined by GPC.
[0088] The polymers prepared with the compositions disclosed herein can have a ratio of weight average molecular weight to number average molecular weight (Mw / Mn) from 2.00 to 6.00. All individual values and subranges from 2.00 to 6.00 are included; for example, the polymer can have a Mw / Mn with a lower limit of 2.00, 2.50, or 3.00 and an upper limit of 6.00, 5.50, or 4.50.
[0089] Various aspects of the disclosure are provided as follows.
[0090] Aspect 1 provides an asymmetric hafnium metallocene represented by structure (I):
[0091]
[0092] Where R 1 is (C1-C8)alkyl; and each X is independently a leaving group.
[0093] Aspect 2 provides the asymmetric hafnium metallocene according to aspect 1, wherein each X is independently a leaving group selected from halogen, (C1-C5) alkyl, CH2SiMe3 and benzyl.
[0094] Aspect 3 provides the asymmetric hafnium metallocene according to any one of aspects 2 to 3, wherein R 1 is (C3-C4)alkyl, and each X is Cl or each X is CH3.
[0095] Aspect 4 provides the asymmetric hafnium metallocene according to aspect 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of:
[0096] Hafnium asymmetric metallocenes represented by structures (II) to (V):
[0097]
[0098] and
[0099]
[0100] Aspect 5 provides the asymmetric hafnium metallocene according to aspect 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of:
[0101] Hafnium asymmetric metallocenes represented by structures (II) to (III):
[0102] and
[0103]
[0104] Aspect 6 provides the asymmetric hafnium metallocene according to aspect 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of:
[0105] Hafnium asymmetric metallocenes represented by structures (IV) to (V):
[0106] and
[0107]
[0108] Aspect 7 provides a method for synthesizing the asymmetric hafnium metallocene according to any one of aspects 1 to 6, wherein each X is Cl, the method comprising:
[0109] The hafnium complex is contacted with an alkali metal complex, wherein the alkali metal complex is represented by the following structure:
[0110]
[0111] wherein M' is lithium, sodium or potassium, and
[0112] Hafnium complexes are represented by one of the following structures:
[0113]
[0114] Where R 1 as defined in the above aspects; or
[0115] The hafnium complex is contacted with an alkali metal complex, wherein the alkali metal complex is represented by the following structure:
[0116]
[0117] Wherein M' is lithium, sodium or potassium, and R 1 as defined in the above aspect; and
[0118] The hafnium complex is represented by the following structure:
[0119]
[0120] To prepare asymmetric hafnium metallocene.
[0121] Aspect 8 provides a method according to aspect 7, which comprises: contacting an asymmetric hafnium metallocene with two molar equivalents of an organic magnesium halide of formula RMg(halide) or one molar equivalent of R2Mg, wherein R is (C1-C5)alkyl, CH2SiMe3 or benzyl; and the halide is Cl or Br, to prepare an asymmetric hafnium metallocene of structure (I), wherein each X is (C1-C5)alkyl, CH2SiMe3 or benzyl.
[0122] Aspect 9 provides a metallocene catalyst composition, the metallocene catalyst composition comprising:
[0123] An asymmetric hafnium metallocene according to any one of aspects 1 to 6, or an asymmetric metallocene prepared by the method according to aspect 7 or aspect 8; and an activator (eg, an alkylaluminoxane, such as methylaluminoxane).
[0124] Aspect 10 provides the metallocene catalyst composition according to aspect 8, further comprising a support (eg, silica, such as hydrophobic fumed silica or dehydrated silica).
[0125] Aspect 11 provides the metallocene catalyst composition according to aspect 10, wherein the composition is a spray-dried metallocene catalyst composition.
[0126] Aspect 12 provides a method for preparing a metallocene catalyst composition according to any one of Aspects 9 to 11, the method comprising: contacting an asymmetric hafnium metallocene with an activator but not with a support to obtain a metallocene catalyst composition according to Aspect 9 without a support; or contacting an asymmetric hafnium metallocene with an activator and a support to obtain a metallocene catalyst composition according to Aspect 10 with a support; or contacting an asymmetric hafnium metallocene with an activator and a support in an inert solvent to obtain a metallocene catalyst composition according to Aspects 10 to 11; or contacting an asymmetric hafnium metallocene with an activator and a support in an inert solvent to obtain a suspension thereof, and spray-drying the suspension to obtain a spray-dried metallocene catalyst composition according to Aspect 11; or contacting an asymmetric hafnium metallocene with a supported or spray-dried activator (or its slurry) in an inert solvent to obtain a spray-dried metallocene catalyst composition according to Aspect 11.
[0127] Aspect 13 provides a method for preparing a polyolefin polymer, the method comprising: polymerizing at least one olefin monomer with the metallocene catalyst composition according to any one of aspects 9 to 11 or the metallocene catalyst composition prepared by the method according to aspect 12 to prepare a polyolefin polymer; wherein preferably, the at least one olefin monomer comprises ethylene and an optional comonomer selected from the group consisting of propylene and (C4-C 20 )α-olefins.
[0128] Aspect 14 provides a method according to aspect 13, wherein the at least one olefin monomer comprises ethylene and a comonomer; and wherein the polyolefin polymer has a molecular weight comonomer distribution index (MWCDI) from 0.10 to 10.00 as measured by the MWCDI test method described herein; wherein preferably, the comonomer is selected from the group consisting of: 1-butene, 1-hexene and 1-octene.
[0129] Aspect 15 provides a polyolefin polymer prepared by the method according to any one of aspects 13 to 14.
[0130] Aspect 16 provides the polyolefin polymer according to aspect 15, wherein the polyolefin polymer has a relationship of MWCDI compared to density such that: MWCDI>-133*density+126.75.
[0131] Aspect 17 provides a polyolefin polymer according to aspect 15, wherein the polyolefin polymer has a relationship of MWCDI compared to density such that: MWCDI>-157.75*density+150.62.
[0132] Aspect 18 provides a method for preparing a polyolefin polymer, the method comprising: polymerizing at least one olefin monomer with a spray-dried asymmetric hafnium metallocene catalyst composition to prepare a polyolefin polymer; wherein the at least one olefin monomer comprises ethylene and an optional comonomer selected from the group consisting of propylene and (C4-C 20 ) alpha-olefins, wherein the polyolefin polymer has a molecular weight comonomer distribution index (MWCDI) from 0.10 to 10.00 and a relationship of MWCDI to density such that: MWCDI>-133*density+126.75.
[0133] Aspect 19 provides the method of aspect 18, wherein the polyolefin polymer has a relationship of MWCDI versus density such that: MWCDI>-157.75*density+150.62.
[0134] Example
[0135] Hafnium Complex I: (n-propylcyclopentadienyl)hafnium trichloride dimethoxyethane adduct represented by the following structure:
[0136]
[0137] Synthesized as follows. (n-propylcyclopentadienyl) hafnium trichloride dimethoxyethane adduct is synthesized as follows (e.g., by adapting the procedure described in WO2016 / 168448A1 of Harlan). Bis-(n-propylcyclopentadienyl) hafnium dichloride is commercially available from TCI; bis(n-propylcyclopentadienyl) hafnium dichloride (25.1 g, 54.1 mmol) is heated to 140 ° C in a 100 mL round-bottom flask until melted. HfCl4 (17.5 g, 54.6 mmol) in the form of a solid powder is added to the flask. The contents of the flask are heated at 140 ° C for about 30 minutes and a brown viscous liquid is formed. The 100 mL round-bottom flask is attached to a short-path distillation apparatus consisting of a glass tube (90 ° bend) attached to a Schlenk flask. Vacuum is drawn through the stopcock of the Schlenk flask. Distillation was performed from 105°C to 110°C under 0.4 torr vacuum. In about one hour, it was observed that most of the material distilled / sublimed into the Schlenk bottle or remained in the glass tube. The solid material in the U-tube was scraped out and merged with the material in the Schlenk bottle. Toluene (50mL) and dimethoxyethane (50mL) were added to the solid. It was heated to reflux to form a solution, and toluene (50mL) was added. Colorless needles were formed after cooling. Pentane (200mL) was added to further form a solid precipitate. The solid was separated by filtration, and the solid was washed with pentane (2x 50mL) and dried under vacuum to provide (n-propylcyclopentadienyl) trichlorohafnium dimethoxyethane adduct (42.2g); the combined supernatant and washings were cooled to obtain another 2.6g product, which was separated.
[0138] Example 1-1 Asymmetric hafnium metallocene, which can be represented by the following structure (II):
[0139]
[0140] is synthesized as follows. For the above formula, as discussed previously, R 1is (C3) alkyl (n-propyl). In a glove box, (n-propylcyclopentadienyl)hafnium trichloride dimethoxyethane adduct (0.75 g, 1.56 mmol) was added to a container (oven dried 4 oz. glass jar); a Teflon coated stirring bar and 40 mL of dry toluene (40 mL) were added to the container and the contents were stirred. The contents were observed to be gray and turbid. Cyclopentadienyl lithium (1 molar equivalent) was slowly added to the container; then, the contents of the container were stirred at about 20° C. for 12 hours. NMR spectroscopy indicated that Example 1-1 was formed as well as some unreacted starting material. The contents of the container were further stirred at about 20° C. for about 120 hours; then, the contents of the container were filtered and the volatiles were removed under reduced pressure. The solid was recrystallized from warm hexane and toluene; the resulting solid (Example 1-1) was isolated (total yield after recrystallization was 63.9%). 1H and 13C NMR spectroscopy confirmed Example 1-1. 1 H NMR (400MHz, C6D6) δ5.86 (s, 3H), 5.77–5.72 (m, 2H), 5.57 (t, J = 2.7Hz, 2H), 2.63–2.54 (m, 2H), 1.48–1.35 (m, 2H), 0.80 (t, J = 7.3Hz, 3H). 13 C NMR (101MHz, C6D6) δ132.81,115.78,114.13,110.86,32.38,24.34,14.00.
[0141] The spray-dried composition of Example 1-2 was prepared as follows. In a nitrogen-purged glove box, hydrophobic fumed silica (CABOSIL TS-610; 1.325 grams) and toluene (37.5 grams) were added to a container and mixed, followed by the addition of a 10% solution (11 grams) by weight of methylaluminoxane (MAO) in toluene. The contents of the container were then stirred for about 15 minutes. Example 1-1 (0.054 grams) was then added to the container and the contents of the container were stirred for about 45 minutes. The contents of the container were then spray dried using a Buchi Mini Spray Drier B-290 (185°C set temperature; 100°C outlet temperature; 150 rpm pump speed) to provide Example 1-2.
[0142] Example 1-3 Asymmetric hafnium metallocene, which can be represented by the following structure (III):
[0143]
[0144] are synthesized as follows.
[0145] Example 1-1 (8.5 g, 20.2 mmol) was dissolved in ether (80 mL) in a container. Methylmagnesium bromide (13.4 mL, 3.0 M in Et2O, 40.3 mmol) was added dropwise to the contents of the container via a syringe; then, the contents of the container were stirred at about 20 ° C for 12 hours. The volatiles were then removed by vacuum, and hexane (30 mL) was added to the contents of the container; the contents were then filtered through diatomaceous earth to remove insoluble by-products. The contents and diatomaceous earth filter were washed with additional hexane (30 mL). The solvent was removed from the filtrate by vacuum to obtain Example 1-3, which was observed to be an off-white solid (7.11 g, 93%). 1 HNMR (400MHz, C6D6): δ5.70(s,4H),5.57(t,J=2.6Hz,2H),5.41(t,J=2.7Hz,2H),2. 33–2.26(m,2H),1.48(dq,J=14.8,7.4Hz,2H),0.87(t,J=7.3Hz,3H),-0.30(s,6H). 13 C NMR (101MHz, C6D6): δ127.08, 110.65, 109.89, 107.39, 36.43, 32.35, 25.22, 14.12.
[0146] 5-(2-methylpropylene)cyclopenta-1,3-diene, which can be represented by the following structure:
[0147]
[0148] Synthesized as follows. In a glove box, pyrrolidine (1.45 g, 10 mol%) was added to a glass container containing a solution of isobutyraldehyde (14.6 g, 203 mmol) and cyclopentadiene (13.4 g, 203 mmol) in MeOH-H2O (200 mL 4 / 1). The contents of the container were transferred to an ice-cold mixture of a saline solution and 10 mol% AcOH in a narrow graduated cylinder. The organic phase was separated and dried over molecular sieves. The product (5-(2-methylpropylidene)cyclopenta-1,3-diene) was filtered to obtain a bright yellow oil, which was then used without further purification (16.0 g, 65%). 1 H NMR (400MHz, CDCl3) δ: 6.54 (tdd, J = 5.4, 3.8, 2.5Hz, 2H), 6.51–6.44 (m, 1H), 6.29–6.17 (m, 2H), 3.02 (dp, J = 10.0, 6.6Hz, 1H), 1.15 (d, J = 6.6Hz, 6H). 13C NMR (101MHz, CDCl3) δ: 149.88, 143.69, 133.08, 130.87, 126.06, 119.36, 30.58, 23.24.
[0149] Isobutylcyclopentadienyllithium, which can be represented by the following structure:
[0150]
[0151] are synthesized as follows.
[0152] Et2O (250 mL) was added to the container. 5-(2-methylpropylidene)cyclopenta-1,3-diene (16.0 g, 133 mmol) was added to the contents of the container while stirring. LiAlH4 (33 mL, 4M Et2O solution) was added dropwise to the contents of the container while stirring. Bubbling was observed. A white solid precipitated during the addition, and the yellow color gradually faded as the LiAlH4 was continued to be added. Addition was stopped once the solution turned only light yellow. The product, isobutylcyclopentadienyllithium, observed as a white solid, was collected by filtration, rinsed with Et2O, and dried under vacuum (13.7 g, 80%).
[0153] Hafnium complex II, which can be represented by the following structure:
[0154]
[0155] are synthesized as follows.
[0156] Isobutylcyclopentadienyl lithium (0.150 g, 1.17 mmol) and hafnium tetrachloride (0.187 g, 0.585 mmol) were added to a container with THF and stirred at about 20 ° C for about 12 hours. The contents of the container were then concentrated to obtain an off-white residue. The residue was extracted with dichloromethane and then filtered. The resulting solution was placed under vacuum to obtain hafnium complex II (0.276 g, 96%). 1 HNMR (400MHz, C6D6) δ: 5.83 (t, J = 2.7Hz, 4H), 5.72–5.61 (m, 4H), 2.57 (d, J = 7.0Hz, 4H), 1.62 (dq, J = 13.5, 6.8Hz, 2H), 0.80 (d, J = 6.6Hz, 12H). 13 C NMR (101MHz, C6D6) δ: 130.67, 116.15, 110.24, 39.50, 30.32, 22.09.
[0157] Hafnium complex III, which can be represented by the following structure:
[0158]
[0159] are synthesized as follows.
[0160] Hafnium tetrachloride (0.33 g, 1.0 mmol) and hafnium complex II bis(isobutylcyclopentadienyl) hafnium dichloride (0.50 g, 1.0 mmol) were combined in a large screw cap container. The contents of the container evolved into a viscous brown liquid when heated. Colorless vapor began to appear on the side of the container at about 150 ° C. At this time, the heating was adjusted to 150 ° C. A white solid began to form at the colorless steam pipe. After about 5 minutes, the container was stopped and cooled under a nitrogen atmosphere. The white solid was manually scraped off the container and transferred to a second container. After removing most of the white solid, the container was placed under vacuum and reheated to 150 ° C for 5 minutes. A second batch of white solids was obtained and combined with the first group of isolated materials to obtain hafnium complex III (0.59 g, 72%). 1 H NMR (400MHz, C6D6) δ5.81 (t, J = 2.7 Hz, 2H), 5.75 (t, J = 2.7 Hz, 2H), 2.27 (d, J = 7.0 Hz, 3H), 1.35 (dq, J = 13.5, 6.7 Hz, 1H), 0.59 (d, J = 6.6 Hz, 8H). 13 C NMR (101MHz, C6D6) δ134.94,116.61,116.04,38.83,30.18,21.67.
[0161] Example 2-1 Asymmetric hafnium metallocene, which can be represented by the following structure:
[0162]
[0163] Was synthesized as follows. Hafnium complex III (0.100 g, 246 mmol) and cyclopentadienyl lithium (0.021 g, 0.246 mmol) were added to a container. Et2O was then added to the container, and the contents of the container were stirred at about 20°C for about 12 hours. The contents of the container were filtered and then concentrated under vacuum to obtain Example 2-1 (0.098 g, 88%). 1H NMR (400MHz, C6D6) δ5.79(t,J=2.7Hz,2H),5.75–5.70(m,1H),5.62(t,J=2.7Hz,1H),5.60(t,J=2.7Hz,1H),2 .54(d,J=7.0Hz,2H),2.25(d,J=2.5Hz,1H),2.18(s,3H),1.60(dq,J=13.5,6.7Hz,1H),0.78(d,J=6.7Hz,6H). 13 C NMR (101MHz, C6D6) δ116.43,116.23,110.71,110.66,39.86,30.71,22.46.
[0164] The spray-dried composition of Example 2-2 was prepared as follows. In a nitrogen-purged glove box, hydrophobic fumed silica (CABOSIL TS-610; 0.665 grams) and toluene (19 grams) were added to a container and mixed, followed by the addition of a 10% solution (5.5 grams) by weight of methylaluminoxane (MAO) in toluene. The contents of the container were then stirred for about 15 minutes. Example 2-1 (0.022 grams) was then added to the container and the contents of the container were stirred for about 45 minutes. The contents of the container were then spray dried using a Buchi Mini Spray Drier B-290 (185°C set temperature; 100°C outlet temperature; 150 rpm pump speed) to provide Example 2-2.
[0165] Comparative Example A-1 A hafnium metallocene having two substituted cyclopentadienyl rings, which can be represented by the following structure:
[0166]
[0167] was synthesized as follows. Bis-(n-propylcyclopentadienyl)hafnium dichloride is commercially available from TCI; one skilled in the art can readily convert it to bis(n-propylcyclopentadienyl)hafnium dimethyl by reaction with a methylating agent such as a Grignard reagent, for example, methylmagnesium bromide.
[0168] Comparative Example A-2 (spray dried composition) was prepared as follows. In a nitrogen purged glove box, hydrophobic fumed silica (CABOSIL TS-610; 2.65 grams) and toluene (75 grams) were added to a container and mixed, followed by the addition of a 10% solution (22 grams) by weight of methylaluminoxane (MAO) in toluene. The contents of the container were then stirred for about 15 minutes. Comparative Example A-1 (0.105 grams) was then added to the container and the contents of the container were stirred for about 45 minutes. The contents of the container were then spray dried using a Buchi Mini Spray Drier B-290 (185°C set temperature; 100°C outlet temperature; 150 rpm pump speed) to provide Comparative Example A-2.
[0169] Comparative Example B-1 A hafnium metallocene having two substituted cyclopentadienyl rings, which can be represented by the following structure:
[0170]
[0171] Was synthesized as follows. In a glove box, (n-propylcyclopentadienyl) hafnium trichloride dimethoxyethane adduct (0.75 grams; 1.56 mmol) was added to a glass jar (4 oz.) containing dry toluene (40 mL) while stirring with a polytetrafluoroethylene-coated stirring bar. The contents of the jar were observed to be gray and turbid. Methylcyclopentadienyl lithium (MeCpLi) (1 molar equivalent) was then slowly added to the contents of the jar, and the contents of the jar were stirred at room temperature (approximately 20° C.) for approximately 12 hours. The contents of the jar were then filtered and volatiles were removed from the filtrate under reduced pressure to provide Comparative Example B-1 (0.618 g; 91.2%). 1H and 13CNMR spectra confirmed the product. 1 H NMR(400MHz,C6D6)δ5.80–5.68(m,3H),5.61(dt,J=5.5,2.7Hz,3H),2.64–2 .55(m,2H),2.17(d,J=0.6Hz,3H),1.49–1.36(m,2H),0.80(t,J=7.4Hz,3H). 13 C NMR (101MHz, C6D6) δ132.51,116.18,115.40,110.75,110.71,32.42,24.39,15.37,14.01.
[0172] Comparative Example B-2 (spray dried composition) was prepared as follows. In a nitrogen purged glove box, hydrophobic fumed silica (CABOSIL TS-610; 1.325 grams) and toluene (37.5 grams) were added to a container and mixed, followed by the addition of a 10% solution (11 grams) by weight of methylaluminoxane (MAO) in toluene. The contents of the container were then stirred for about 15 minutes. Comparative Example B-1 (0.056 grams) was then added to the container and the contents of the container were stirred for about 45 minutes. The contents of the container were then spray dried using a Buchi Mini Spray Drier B-290 (185°C set temperature; 100°C outlet temperature; 150 rpm pump speed) to provide Comparative Example B-2.
[0173] Comparative Example C-1 (spray-dried composition) was prepared as follows. In a nitrogen-purged glove box, hydrophobic fumed silica (CABOSIL TS-610; 1.33 grams) and toluene (37.5 grams) were added to a container and mixed, followed by the addition of a 10% solution (11 grams) by weight of methylaluminoxane (MAO) in toluene. The contents of the container were then stirred for about 15 minutes. Hafnium complex II (0.049 grams) was then added to the container and the contents of the container were stirred for about 45 minutes. The contents of the container were then spray dried using a Buchi Mini Spray Drier B-290 (185°C set temperature; 100°C outlet temperature; 150 rpm pump speed) to provide Comparative Example C-1.
[0174] Polymerization is performed as follows. For the corresponding polymerization, dry NaCl (200 g) is loaded into a laboratory-level gas phase polymerization reactor (equipped with a 2-liter stainless steel autoclave with a variable speed mechanical stirrer) and heated to 100 ° C for one hour under a nitrogen stream. The reactor is then purged with nitrogen, methylaluminoxane supported by silica is added to the reactor as a scavenger, the reactor temperature is adjusted to an approximately desired temperature, the reactor is sealed, and the contents of the stirring reactor are stirred. The reactor is preloaded to the desired pressure with hydrogen, ethylene and 1-hexene. When steady state is reached, the catalyst is loaded into the reactor (at the temperature indicated below) to start polymerization. The reactor temperature is maintained at the desired temperature for 60 minutes of polymerization, wherein hydrogen, C6 / C2 ratio and ethylene pressure are kept constant. At the end of 60 minutes of polymerization, the reactor is cooled, vented and opened. The resulting mixture is washed with water and methanol and dried. The polymerization conditions are reported in Table 1 to Table 4.
[0175] Various properties of the polymers prepared using Examples 1-2, Example 2-2, Comparative Example A-2, Comparative Example B-2, and Comparative Example C-1, respectively, were determined. The results are reported in Tables 1 to 4. The polymerization productivity (gram polymer / gram catalyst-hour) was determined as the ratio of the polymer produced to the amount of catalyst added to the reactor. The melt index (I2) was determined according to ASTM D1238 (190°C, 2.16 kg), the melt index (I5) was determined according to ASTM D1238 (190°C, 5 kg), and the melt index (I 21 ) was determined according to ASTM D1238 (190°C, 21.6 kg). Melt temperature was determined using differential scanning calorimetry according to ASTM D 3418-08, using a scan rate of 10°C / min for a 10 mg sample and using the second heating cycle to determine T m . M w 、M n 、M z 、M w / M n (PDI) and M z / M w The comonomer content (e.g., 1-hexene) incorporated into the polymer is determined by fast FT-IR spectroscopy of the dissolved polymer in a GPC measurement, as discussed above in the detailed description; the molecular weight comonomer distribution index (MWCDI) is determined as discussed herein.
[0176] Table 1
[0177]
[0178] The data of Table 1 illustrate that the polymer prepared with Example 1-2 has an improved (i.e., greater) molecular weight comonomer distribution index (MWCDI) compared to the polymer prepared with both Comparative Example A-2 and Comparative Example B-2. In addition, the polymer prepared by Example 1-2 has a higher Mw under the same conditions, which is also shown by: having a no flow melt index (I2) compared to 0.863 and 0.761 for the polymer prepared by Comparative Examples A-2 and B-2, and having a much lower flow index than the polymer prepared by Comparative Examples A-2 or B-2. Catalyst Example 1-2 also incorporates more comonomer under the same conditions as Comparative Examples A-2 and B-2, such as being prepared as a polymer of a higher weight % of hexene than any of the Comparative Examples.
[0179] Figure 1Shown are data graphs for determining the MWCDI for the polymer prepared with Example 1-2 (MWCDI = 6.58), and data graphs for determining the MWCDI for the polymer prepared with Comparative Example A-2 (MWCDI = 3.60), as reported in Table 1.
[0180] Table 2
[0181]
[0182]
[0183] The data in Table 2 illustrate that the polymer prepared with Example 1-2 has an improved (i.e., greater) molecular weight comonomer distribution index (MWCDI) compared to the polymers prepared with both Comparative Example A-2 and Comparative Example B-2. The polymer prepared with Example 1-2 also has a higher Mw, which is also shown by the following: a lower flow index (I21) compared to the polymers prepared by Comparative Example A-2 or B-2. Catalyst Example 1-2 also incorporates more comonomer under the same conditions as Comparative Examples A-2 and B-2, such as preparing a polymer with a higher weight % of hexene than any of the Comparative Examples.
[0184] Table 3
[0185]
[0186]
[0187] The data in Table 3 illustrate that the polymer prepared with Example 2-2 has an improved (i.e., greater) molecular weight comonomer distribution index (MWCDI) compared to the polymers prepared with both Comparative Example A-2 and Comparative Example C-1. In addition, in Tables 3 and 4, Example 2-2 is shown to have a higher Mw under the same conditions - this higher Mw capability is a desirable feature of the catalysts disclosed herein.
[0188] Figure 2 Shown are data graphs for determining the MWCDI for the polymer prepared with Example 2-2 (MWCDI = 7.38), and data graphs for determining the MWCDI for the polymer prepared with Comparative Example A-2 (MWCDI = 3.60), as reported in Table 3.
[0189] Table 4
[0190]
[0191]
[0192] The data in Table 4 illustrate that the polymer prepared with Example 2-2 has an improved (ie, greater) molecular weight comonomer distribution index (MWCDI) compared to the polymers prepared with both Comparative Example A-2 and Comparative Example C-1.
[0193] The polymer was prepared using a gas phase continuous polymerization reactor as follows, wherein multiple polymerizations utilized a conditioning component (having a concentration of 0.04 wt%).
[0194] Spray dried MAO slurry (SDMAO) - 14 wt% SDMAO, 10 wt% hexane, 76 wt% Hydrobite 380 mineral oil (obtained from Sonneborn, LLC). Spray dried MAO was prepared as a dry powder by adapting the procedure according to US 8,497,330 B2, column 22, lines 48 to 67. The adapted procedure omits the addition of the metallocene compound; instead, toluene, methylaluminoxane (MAO available from AkzoNobel), Cabosil slurry were introduced into the atomizing apparatus to produce SDMAO as a dry powder. The polymerization conditions are reported in Tables 5, 7 and 8.
[0195] The spray dried compositions of Examples 1-4 were prepared as follows. In a 13 gallon mixing tank, 2.38 lbs of Cabosil TS-610 hydrophobic fumed silica and 37.0 lbs of a 10 wt% MAO solution in toluene were slurried, and then 80.0 g of (propylcyclopentadienyl)(cyclopentadienyl)hafnium(IV) dichloride (Example 1-1) was slurried with an additional 20 lbs of toluene. The mixture was spray dried using the following operating parameters: inlet temperature 146°C, outlet temperature 84°C, slurry inlet feed 13 lb / hr, and atomizer speed 20,000 revolutions per minute (rpm) to obtain 4.1 lbs of Example 1-4 as a powder.
[0196] The spray-dried composition of Example A-3 was prepared as described above (same procedure as for Examples 1-4) and adapted according to the procedure of US 8,497,330 B2, column 22, lines 48 to 67. Example A-1 was slurried with hydrophobic fumed silica, a solution of MAO in toluene and additional toluene and then introduced into an atomizing apparatus as described for Examples 1-4 to obtain Example A-3 as a powder.
[0197] A number of properties were determined for the polymers. The results are reported in Tables 6, 9, 10 and 11. The polymerization productivity (gram polymer / gram catalyst-hour) was determined as the ratio of the polymer produced to the amount of catalyst added to the reactor. The melt index (I2) was determined according to ASTM D1238 (190°C, 2.16 kg), the melt index (I5) was determined according to ASTM D1238 (190°C, 5 kg), and the melt index (I21) was determined according to ASTM D1238 (190°C, 21.6 kg); Mw, Mn, Mz and Mw / Mn were determined by GPC; the molecular weight comonomer distribution index (MWCDI) was determined as discussed herein.
[0198] Polymerization utilizes an experimental fluidized bed gas phase polymerization reactor, which includes a reactor vessel containing a fluidized bed of ethylene / alpha-olefin copolymer powder and a distributor plate disposed above the bottom end cap, and defines a bottom gas inlet at the top of the reactor vessel and has an expansion section or a cyclone system to reduce resin fines that may escape from the fluidized bed. The expansion section defines a gas outlet. The reactor also includes a compressor blower, which is used to pass a circulation loop downward to and into the bottom gas inlet of the reactor from the gas outlet in the expansion section in the top of the reactor vessel and through the distributor plate and the fluidized bed. The reactor also includes a cooling system, which removes polymerization heat and keeps the fluidized bed at a target temperature. In the circulation loop, a composition of gas (such as ethylene, alpha-olefin and hydrogen) is fed into the reactor and monitored by an online gas chromatograph to maintain a specific concentration for controlling polymer properties. The spray-dried catalyst is fed into the reactor from a high pressure device in the form of a slurry or dry powder, wherein the slurry is fed via a syringe pump and the dry powder is fed via a quantitative disk. The catalyst enters the fluidized bed in the lower 1 / 3 of the bed height.The polymerization system weighs the fluidized bed and includes a separation orifice that discharges polymerization product from the reactor vessel in response to the fluidized bed weight increasing as the polymerization reaction proceeds.
[0199] Table 5
[0200]
[0201]
[0202] Table 6
[0203] Gas Phase Continuous Polymer 1 Gas Phase Continuous Polymer 2 Gas Phase Continuous Polymer 3 Mn 106,534 73,499 131,629 M 355,639 217,821 435,616 Mz 899,605 495,113 1,140,739 Peak molecular weight 249,126 150,227 322,909 PDI 3.34 2.96 3.31 Mz / Mw 2.53 2.27 2.62 C6 weight% 1.2 1.4 1.7 SCB / 1000TC 1.53 1.81 1.99 MWCDI 1.58 0.03 0.82 Tm(℃) 133.1 127.5 132.9 ΔHm(J / g) 119.7 140.5 109.2
[0204] Tables 5 and 6 refer to polymers prepared using Examples 1-3 as adjustments to SDMAO. The target for each of the gas phase continuous polymers 1 to 3 was the same density and was21 When the molecular weight is 0.5, it has a similar molecular weight.
[0205] Gas-continuous polymer 2 prepared with Comparative Example A-2 was only able to prepare polymer at 3FI (about 218 kMw), which is the upper limit of the catalyst molecular weight capacity. Gas-continuous polymer 1 and gas-continuous polymer 2 have similar FI and Mw (with a small difference due to the slightly higher H2 / C2 for gas-continuous polymer 1) and density. The density of each polymer is approximately equal, and the polymers in Tables 5 and 6 can be referred to as having medium density.
[0206] Comparison of the gas-continuous polymer 1 prepared using Examples 1-3 with gas-continuous polymers 2 to 3 shows that Examples 1-3 are capable of preparing polymers in the medium density range and at very high molecular weights (I 21 The data in Table 6 illustrate that the polymers prepared with Examples 1-3 have an improved (i.e., greater) molecular weight comonomer distribution index (MWCDI) compared to the polymers prepared with both Comparative Example A-3 and Comparative Example C-1.
[0207] Figure 3A Shown are data graphs for determining the MWCDI for gas phase continuous polymer 1 (MWCDI = 1.58), and data graphs for determining the MWCDI for gas phase continuous polymer 2 (MWCDI = 0.03), as reported in Table 6.
[0208] Figure 3B Shown are data graphs for determining the MWCDI for gas phase continuous polymer 1 (MWCDI = 1.58), and data graphs for determining the MWCDI for gas phase continuous polymer 3 (MWCDI = 0.82), as reported in Table 6.
[0209] Table 7
[0210]
[0211]
[0212] Table 8
[0213]
[0214] Gas phase continuous polymers 10 to 13 were prepared using XCAT VP-100 obtained from Univation Technologies, LLC and used herein as a comparative catalyst. VP-100 is a supported catalyst consisting of symmetric hafnium metallocene Example A-1.
[0215] Table 9
[0216] Gas Phase Continuous Polymer 4 Gas Phase Continuous Polymer 5 Gas Phase Continuous Polymer 9 I2 melt index [dg / min] 0.208 0.364 0.33 I21 flow index [dg / min] 7.575 11.33 6.732 Melt flow ratio (I21 / I2) 36.3 31.13 20.4 Density [g / cc] 0.9189 0.9234 0.9188 Mn 47,140 38,096 47901 M 195,127 148,915 157,738 Mz 645,780 460,523 377,041 Peak molecular weight 72,444 67,608 91280 PDI 4.14 3.91 3.29 Mz / Mw 3.31 3.09 2.39 C6 weight% 9.87 7.65 6.26 SCB / 1000TC 16.45 12.74 7.14 MWCDI 7.34 5.4 2.51 Tm(℃) 8.00 5.49 3.35 ΔHm(J / g) 120.7 132.8 119.1 Melt strength, force (cN) 14.7 13.8 9.5 Pullability (mm / s) 99.3 79.2 61.3 V0.1, Pa·s 74689 57169 21147 V100, Pa·s 2968 2526 3380 RR=V0.1 / V100 25.16 22.63 6.26
[0217] The gas phase continuous polymers of Table 9 may be referred to as linear low density polymers.
[0218] The data in Table 9 illustrate that the polymers prepared with Examples 1-4 and Example 1-3 / SDMAO each have an improved (ie, greater) molecular weight comonomer distribution index (MWCDI) at equivalent density and MI compared to the polymer prepared with Comparative Example A-3.
[0219] Figure 4 Shown are data graphs for determining the MWCDI for gas phase continuous polymer 4 (MWCDI = 7.34), and data graphs for determining the MWCDI for gas phase continuous polymer 9 (MWCDI = 2.51), as reported in Table 9.
[0220] Compared with the melt strength of 9.5cN of the gas-phase continuous polymer 9 prepared by Comparative Example A-1, the gas-phase continuous polymers 4 and 5 prepared by Examples 1-4 and Example 1-3 / SDMAO each have the improved melt strength (that is, greater melt strength) of 14.2cN and 13.8cN respectively. Compared with the comparative gas-phase continuous polymer 9 prepared by Comparative Example A-3, gas-phase continuous polymers 4 and 5 also have improved melt flow ratio (I21 / I2) (that is, greater melt flow ratio (I21 / I2)) and wider PDI in addition. Compared with the comparative gas-phase continuous polymer 9, gas-phase continuous polymers 4 and 5 both have improved high shear viscosity (V100) (i.e. reduced high shear viscosity (V100)), although with significantly higher low shear viscosity (V0.1). Lower high shear viscosity (V100) is usually associated with improved processing rate, which is advantageous. The rheological ratio (RR) of gas-phase continuous polymers 4 and 5 prepared with catalyst examples 1-4 and example 1-3 / SDMAO is significantly greater than the RR of gas-phase continuous polymer 9 prepared by comparative example A-3. A higher RR indicates that the polymer has a higher degree of shear thinning. In summary, the improved melt strength, increased shear thinning, larger MFR, wider PDI and lower high shear viscosity (V100) for gas-phase continuous polymers 4 and 5 prepared with catalyst examples 1-4 and example 1-3 / SDMAO all indicate improved processability for applications (such as films) within this density range compared to gas-phase continuous polymer 9 prepared by comparative example A-3.
[0221] The data in Table 9 demonstrate that Catalyst Examples 1-4 and Example 1-3 / SDMAO can produce polymers with improved mechanical properties as well as improved processability, which is a very favorable balance of properties.
[0222] Table 10
[0223] Gas Phase Continuous Polymer 6 Gas Phase Continuous Polymer 10 Gas phase continuous polymer 12 I2 melt index [dg / min] 6.915 7.1845 3.389 I21 flow index [dg / min] 143.648 131.3951 57.27 Melt flow ratio (I21 / I2) 20.78 18.3 16.9 Density [g / cc] 0.9355 0.9349 0.9391 Mn 23,222 23,359 31790 M 65,553 66,082 84892 Mz 150,880 129,920 168285 Peak molecular weight 46,774 53,703 56,234 PDI 2.82 2.83 2.67 Mz / Mw 2.3 1.97 1.98 C6 weight% 4.62 3.21 1.7 SCB / 1000TC 7.7 4.14 2.36 MWCDI 3.56 1.17 0.79 Tm(℃) 123.3 122.71 - ΔHm(J / g) 162 173.1 - V0.1, Pa·s 1771 1084 2321 V100, Pa·s 622 640 1103 <![CDATA[RR1=V0.1 / V100]]> 2.85 1.69 2.10
[0224] The gas phase continuous polymers of Table 10 can be referred to as medium density polymers.
[0225] The data in Table 10 illustrate that the polymers prepared using Examples 1-4a have improved (ie, greater) molecular weight comonomer distribution indices (MWCDI) compared to the polymers prepared using VP-100.
[0226] Figure 5 Shown are data graphs for determining the MWCDI for gas phase continuous polymer 6 (MWCDI = 5.36), and data graphs for determining the MWCDI for gas phase continuous polymer 10 (MWCDI = 1.17), as reported in Table 9.
[0227] Gas-continuous polymer 6 has an improved high shear viscosity (V100) (i.e., a reduced high shear viscosity (V100)) despite having a significantly higher low shear viscosity (V0.1) compared to comparative gas-continuous polymers 10 and 12. Gas-continuous polymer 6 prepared by using Examples 1-4 also has an improved rheological ratio (RR) (i.e., a greater rheological ratio (RR) ratio) compared to gas-continuous polymers 10 and 12 prepared by comparative catalyst VP-100.
[0228] Table 11
[0229]
[0230] The gas phase continuous polymers of Table 11 can be referred to as high density polymers.
[0231] The data in Table 11 illustrate that the polymers prepared with Example 1-1a have improved (i.e., greater) molecular weight comonomer distribution index (MWCDI) compared to polymers prepared with VP-100 at a given density range. For example, gas-continuous polymer 7 prepared with Example 1-4 has a greater MWCDI (2.65) than gas-continuous polymer 11 prepared with VP-100 (MWCDI=0.34), and both polymers have a density of 0.942 g / cc to 0.943 g / cc. Likewise, at even higher densities, gas-continuous polymer 8 prepared with Example 1-4 has a greater MWCDI (0.26) at 0.9551 g / cc compared to gas-continuous polymer 13 prepared with VP-100 (MWCDI=0.34) at 0.952 g / cc.
[0232] Figure 6 Shown is a data graph of molecular weight comonomer distribution index (MWCDI) versus density according to various embodiments of the present disclosure. Figure 6 It is a graph of molecular weight comonomer distribution index (MWCDI) versus density for inventive gas-continuous polymers 4 to 8 and comparative gas-continuous polymers 9 to 13. Gas-continuous polymers 4 to 8 were all prepared by spray-dried catalysts (adjusted or otherwise) containing an asymmetric hafnium metallocene having one n-propylcyclopentadienyl ligand and one unsubstituted cyclopentadienyl ligand (i.e., Examples 1-1 and 1-3). Gas-continuous polymers 9 to 13 were all prepared by spray-dried catalysts or supported commercial catalyst VP-100, all of which contained comparative symmetric hafnium metallocene having two n-propylcyclopentadienyl ligands (i.e., Example A-1).
[0233] Figure 6 The data illustrate that the polymers prepared by the catalysts consisting of Examples 1-1 and 1-3 exhibit improved (ie, greater) MWCDI at a given density compared to the polymer prepared by the catalyst consisting of Comparative Symmetric Metallocene Example A-1.
[0234] Examples 1-1 and 1-3 produced polymers having a MWCDI vs. density relationship such that: MWCDI = -182.51*density + 174.5. The comparative catalyst produced polymers having a MWCDI vs. density relationship such that: MWCDI = -82.45*density + 78.235.
[0235] In some embodiments, the catalysts of the present invention exhibit a relationship of MWCDI versus density such that: MWCDI > -133*density + 126.75.
[0236] Figure 7 Shown is a data graph of molecular weight comonomer distribution index (MWCDI) versus density according to various embodiments of the present disclosure. Figure 7 Graph of molecular weight comonomer distribution index (MWCDI) versus density for inventive gas-continuous polymers 4 to 8 and comparative gas-continuous polymers 9 to 13. Gas-continuous polymers 4 to 8 were all prepared by spray-dried catalysts (adjusted or otherwise) containing an asymmetric hafnium metallocene having one n-propylcyclopentadienyl ligand and one unsubstituted cyclopentadienyl ligand (i.e., Examples 1-1 and 1-3). Gas-continuous polymers 9 to 13 were all prepared by spray-dried catalysts or supported commercial catalyst VP-100, all of which contained comparative symmetric hafnium metallocene having two n-propylcyclopentadienyl ligands (i.e., Example A-1). As Figure 7 As shown, one or more embodiments provide that the catalyst of the present invention provides a relationship of MWCDI compared to density such that: MWCDI>-157.75*density+150.62, such as Figure 7 shown.
Claims
1. An asymmetric hafnium metallocene represented by structure (I): Where R 1 is (C1-C8)alkyl; and each X is independently a leaving group.
2. The asymmetric hafnium metallocene according to claim 1, wherein each X is independently a leaving group selected from halogen, (C1-C5) alkyl, CH2SiMe3 and benzyl.
3. The asymmetric hafnium metallocene according to any one of claims 2 to 3, wherein R 1 is (C3-C4)alkyl, and each X is Cl or each X is CH3.
4. The asymmetric hafnium metallocene according to claim 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of: Hafnium asymmetric metallocenes represented by structures (II) to (V):
5. The asymmetric hafnium metallocene according to claim 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of: Hafnium asymmetric metallocenes represented by structures (II) to (III):
6. The asymmetric hafnium metallocene according to claim 1, wherein the asymmetric hafnium metallocene is selected from the group consisting of: Hafnium asymmetric metallocenes represented by structures (IV) to (V):
7. A method for synthesizing an asymmetric hafnium metallocene according to any one of claims 1 to 6, wherein each X is Cl, the method comprising: The hafnium complex is contacted with an alkali metal complex, wherein the alkali metal complex is represented by the following structure: wherein M' is lithium, sodium or potassium, and The hafnium complex is represented by one of the following structures: Where R 1 as defined in the preceding claims; or The hafnium complex is contacted with an alkali metal complex, wherein the alkali metal complex is represented by the following structure: Wherein M' is lithium, sodium or potassium, and R 1 As defined in the above claims; and The hafnium complex is represented by the following structure: To prepare the asymmetric hafnium metallocene.
8. The method according to claim 7, comprising: The asymmetric hafnium metallocene is contacted with two molar equivalents of an organomagnesium halide of formula RMg(halide) or one molar equivalent of R2Mg, wherein R is (C1-C5)alkyl, CH2SiMe3 or benzyl; and the halide is Cl or Br, to prepare an asymmetric hafnium metallocene of structure (I), wherein each X is (C1-C5)alkyl, CH2SiMe3 or benzyl.
9. A metallocene catalyst composition, comprising: The asymmetric hafnium metallocene according to any one of claims 1 to 6, or the asymmetric metallocene prepared by the method according to claim 7 or claim 8; and Activator. 10 . The metallocene catalyst composition according to claim 9 , further comprising a carrier.
11. The metallocene catalyst composition of claim 10, wherein the composition is a spray-dried metallocene catalyst composition.
12. A method for preparing a metallocene catalyst composition according to any one of claims 9 to 11, the method comprising: contacting the asymmetric hafnium metallocene with the activator but without the support to obtain the metallocene catalyst composition according to claim 9 without a support; Alternatively, the asymmetric hafnium metallocene is contacted with the activator and the support to obtain the metallocene catalyst composition according to claim 10 with the support; or the asymmetric hafnium metallocene is contacted with the activator and the support in an inert solvent to obtain the metallocene composition according to claims 10 to 11; or the asymmetric hafnium metallocene is contacted with the activator and the support in an inert solvent to obtain a suspension thereof, and the suspension is spray-dried to obtain the spray-dried metallocene catalyst composition according to claim 11; or the asymmetric hafnium metallocene is contacted with a supported or spray-dried activator (or its slurry) in an inert solvent to obtain the spray-dried metallocene catalyst composition according to claim 11.
13. A method for preparing a polyolefin polymer, the method comprising: at least one olefin monomer is polymerized with the metallocene catalyst composition according to any one of claims 9 to 11 or the metallocene catalyst composition prepared by the method according to claim 12 to prepare the polyolefin polymer; wherein preferably, the at least one olefin monomer comprises ethylene and optionally a comonomer selected from the group consisting of propylene and (C4-C 20 )α-olefins.
14. The method of claim 13, wherein the at least one olefin monomer comprises ethylene and the comonomer; and wherein the polyolefin polymer has a molecular weight comonomer distribution index (MWCDI) from 0.10 to 10.00 as measured by the MWCDI test method described herein; wherein preferably, the comonomer is selected from the group consisting of: 1-butene, 1-hexene and 1-octene.
15. A polyolefin polymer prepared by the process according to any one of claims 13 to 14.
16. The polyolefin polymer of claim 15, wherein the polyolefin polymer has a relationship of MWCDI versus density such that: MWCDI>-133*density+126.
75.
17. The polyolefin polymer of claim 15, wherein the polyolefin polymer has a relationship of MWCDI versus density such that: MWCDI > -157.75*density + 150.
62.
18. A method for preparing a polyolefin polymer, the method comprising: polymerizing at least one olefin monomer with a spray-dried asymmetric hafnium metallocene catalyst composition to produce the polyolefin polymer; wherein at least one olefin monomer comprises ethylene and optionally a comonomer selected from the group consisting of propylene and (C4-C 20 ) alpha-olefins, wherein the polyolefin polymer has a molecular weight comonomer distribution index (MWCDI) from 0.10 to 10.00 and a relationship of MWCDI to density such that: MWCDI>-133*density+126.
75.
19. The method of claim 18, wherein the polyolefin polymer has a structure such that: MWCDI>-157.75*density+150.62 MWCDI compared to density.
Citation Information
Patent Citations
Methods for polymerization using spray dried and slurried catalyst
US8497330B2
Method for synthesis of monocyclopentadienyl complexes of zirconium and hafnium
WO2016168448A1